Proposed new scheme for Rumah Peranginan Persekutuan at Km 18, Jalan Pantai, Si Rusa, 71050, Port Dickson, Negeri Sembilan Darul Khusus / Nurul Adyla Abdul Hady - Abdul hady, Nurul Adyla (Faculty of Architecture, Planning and Surveying, 2008)
The final project for the interior design for diploma menifestation is for students’ understanding on the process of design aspects that has been studied from the basic to the presentation level of the design proposal.The chosen project is hospitality .which is proposing a new scheme for the federal government’s rest house,Rumah Peranginan Persekutuan.The purpose of this project is to bring a whole new perception towards a typical government’s rest house and at the same time upgrade the image and concept,to create and environment that is more like a tropical resort and has a characteristics of energy eficiency in design which relates to sustainable design.In running this project,the most important thing is the fundamentals of a rest house and resort,finding the images and the application on implying sustainability in design.The advatage can be seen by conserving nature,letting the rest house fuses in with the surroundings.The usage of different materials are discovered to suit with the requirements of sustainable design.The new scheme of design for the rest house will atrract more guests and also the tropical ambience will make the environment more soothing and calm.In conclusion.the new design concept that will be appllied should have the characteristics and guests’ needs.The design hopefully will change the perception of a typical government’s rest house and at the same time bring benefits to guests and workers.